ANALISIS PENTINGNYA KESELAMATAN DAN KESEHATAN KERJA (K3) DALAM MENINGKATKAN MUTU PRODUK MELALUI QUALITY CONTROL DI PT DAMI SARIWANA, TANGERANG SELATAN - Rani Ermawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Occupational Safety and Health (OSH) plays an important role in creating a safe working environment and supporting Quality Control to achieve optimal product quality. This study aims to analyze the implementation of OSH, its role in supporting Quality Control, and its relationship with product quality at PT Dami Sariwana, South Tangerang. A qualitative case study approach was employed. Data were collected through in-depth interviews, observations, documentation, and Focus Group Discussions involving eight informants consisting of production operators, Packaging Leader, Quality Control staff, managers, and the Technical Person in Charge Pharmacist. Data were analyzed using the Miles and Huberman interactive model. The findings indicate that OSH implementation has not been fully optimized, as reflected by inconsistent use of personal protective equipment, crowded work areas, inadequate machine maintenance, poor waste management, and limited occupational health facilities. These conditions affect the effectiveness of Quality Control by reducing workers' accuracy during production. Nevertheless, the company maintains product quality through supervision of raw materials, production processes, and finished products according to Standard Operating Procedures. The study concludes that integrating OSH with Quality Control is essential for improving product quality consistency.